Bacterioplankton dynamics during winter freezing in a meltwater pond near Bratina Island, Antarctica - Noell, Stephen E.; Archer, Stephen D. J.; Hawes, Ian; Cary, S. Craig; McDonald, Ian R. (Frontiers in Microbiology, 2026)
The Bratina Island meltwater ponds, on the Ross Ice Shelf in Antarctica, undergo an annual freeze thaw cycle that results in progressive, extreme changes to the physical and chemical environments of the ponds. Here, we present the first investigation of the microbial community changes during this period using 16S rRNA gene sequence data from across the water column of Legin Pond, a stratified meltwater pond, from four time points that span the autumnal freeze period (January to April 2008). We found that the microbial community changed with the onset of winter, although water column depth and conductivity were also important factors influencing the community composition. We discovered a dominant presence of ASVs from the poorly characterized archaeal phylum “Nanoarchaeota” (now Nanobdellota), with abundance increasing with the onset of winter up to 95% of the total community at the final time point. Conversely, we observed a decrease over time in presumed aerobic, chemoorganotrophic groups from the phyla Bacteroidota, Actinomycetota, and Pseudomonadota (especially the Alphaproteobacteria class Paracoccaceae). Combined with previous complimentary physicochemical observations, our results paint a picture of a pond shifting from a mixed-layer community (part low-salinity enigmatic Archaea, part saltwater aerobic chemoorganotrophs) to a predominantly highly saline Archaea community that may have relied on heterotrophy to survive as the last of the pond water froze with the onset of winter.